مفهوم الاصلاح وفق المنظور الفكري الاسلامي - سعيد, إسماعيل دهله هايش; صالح, عمار منصور عبد النبي; صالح, عمار باسم (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
Reform is one of the most widely discussed “concepts”, and it is still continuing and the views on it vary. Rather, you find that it is a subject that reformers and philosophers have always dealt with on the one hand. Indeed, it was the focus of heavenly messages. It is necessary to have an integrated conception of what the concept of reform is, because it is the focus of study, in order to identify the mechanisms and approaches. adopted, especially in the Islamic approach, as the concept of reform is one of the concepts of the social sciences, thorny and intertwined, based on the perspective of the party carrying out the reform, in addition to the fact that it takes place in all areas of political, social, economic, moral, and educational life. The research pointed out that reform is a preliminary attempt to explore the reality of reform and its concept in Islam, and to describe the presence of educational practices in the Arab-Islamic heritage, as the importance of this research lies in identifying a group of important issues related to the contemporary Islamic reform system, between the research to explain the extent of the need for values Authentic reformist education that draws its reference from the origins of Islam. The research excelled in diagnosing and analyzing the concept of the reform system in Islam, and highlighting its importance in the new and contemporary Islamic system. The research confirmed that reconciliation among Muslims and reconciling their hearts to the truth is something that must be observed, and is considered one of the greatest rules of the religion. The research concluded that reconciliation between people has means and methods that those in charge should know and use according to the facts and circumstances.